On the Multidimensionality of Teachers’ Qualities, Personal Achievement, and their Role in Students’ Achievement in General Mathematics - Melchor, Peter John M.; Suana, Emma O.; Saldivar, John Mark N. (International Journal of Scientific Research and Management (IJSRM), 2025)
This study was conducted to develop a valid and reliable tool that can be used to measure teachers' qualities and create a robust ordinal logistic regression model that predicts students' achievement in General Mathematics based on teachers' qualities and achievements as independent variables. The statistical tools used were the Reliability Test, Exploratory Factor Analysis, and Ordinal Regression Analysis. The researcher interviewed ten experienced mathematics teachers and ten senior high school students who recently finished General Mathematics. Their responses were then converted to measurable variables to construct an initial questionnaire. The initial questionnaire was pilot tested on 300 student respondents for reliability and was found reliable. Based on the results under Exploratory Factor Analysis, there are five latent variables/dimensions of teachers' qualities. These dimensions are Instructional Competencies, Personal Qualities, Procedural Fairness on Tests, Handling Learners' Response, and Compassionate Discipline. Moreover, the result of ordinal regression analysis explained five explanatory predictors that have significantly improved the Logistic Ordinal Regression Model. These five explanatory predictors were the Teacher's Years of Experience, the Teacher's Highest Educational Attainment, Personal Qualities, Procedural Fairness on Tests, and Handling Learners' Responses. With the highest Wald value of 5.842, Teachers' Personal Qualities significantly influenced student achievement in General Mathematics. Hence, teachers' attitudes in dealing with students should be seriously considered when aiming to increase the level of students' achievement in mathematics.